Radioatividade : o processo transitório do medo à ideia de cura pelas areias monazíticas - Coelho, Marina Meira (2022)
The research Radioactivity: the transitory process from fear to the idea of healing by the monazitic sands, we investigated from the monazite sands, a spontaneous radioactivity emitter in the city of Guarapari-ES; the fear process, which was widely publicized by the media, causing strangeness, and the idea of healing promoted by radioactivity. As a methodological basis, we used a specific bibliography on the development of Science in Brazil, in addition to newspapers and documents already made available by the Brazilian Armed Forces, mainly the Navy. Research in the Public Archives proved to be essential, as it is where information about the monazite sands of Brazil and the places where their elements were industrially processed are recorded. At the end of the research, we saw that the media and fear, together with the general lack of specific knowledge that society had about what radioactivity is, provoked dubious interpretations. Interviews were also applied, which sought to understand how and if the transition from the fear process to the healing of the people who passed and inhabited that place actually took place, through the components of the monazite sands.